LEGAL ANALYSIS ON THE IMPLEMENTATION OF CORPORATE SOCIAL AND ENVIRONMENTAL RESPONSIBILITY BY REGIONAL GOVERNMENTS - Roman Situngkir (NOMOI Law Review, 2020)
In Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies, it is stated that, Companies that carry out their business activities in the field and / or related to natural resources are required to carry out social and environmental responsibility, these obligations are budgeted and calculated as the company's costs. carried out with due regard to appropriateness and reasonableness and if the obligation is not carried out, then it will be subject to sanctions in accordance with the provisions of the prevailing laws and regulations.Referring to this provision, this authority is the authority of the central government.However, if we refer to Law Number 23 of 2014 concerning Regional Government, it also has authority in the social and environmental fields.So that in this paper we will examine the extent of regional authority in terms of corporate social and environmental responsibility in the regions.The research method used is normative juridical legal research.The results of the study show that the authority of local governments regarding corporate social and environmental responsibility is not clearly stated in Law Number 23 of 2014 concerning Regional Government.However, based on the principle of regional autonomy, local governments can exercise powers that are not absolutely the authority of the central government.Therefore, in the future, the regional government authority has a strong legal basis so that the authority regarding corporate social and environmental responsibility is contained in statutory regulations.Keywords: Responsibility, Social, Company, Local Government.In Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies, it is stated that, Companies that carry out their business activities in the field and / or related to natural resources are required to carry out social and environmental responsibility, these obligations are budgeted and calculated as the company's costs. carried out with due regard to appropriateness and reasonableness and if the obligation is not carried out, then it will be subject to sanctions in accordance with the provisions of the prevailing laws and regulations.Referring to this provision, this authority is the authority of the central government.However, if we refer to Law Number 23 of 2014 concerning Regional Government, it also has authority in the social and environmental fields.So that in this paper we will examine the extent of regional authority in terms of corporate social and environmental responsibility in the regions.The research method used is normative juridical legal research.The results of the study show that the authority of local governments regarding corporate social and environmental responsibility is not clearly stated in Law Number 23 of 2014 concerning Regional Government.However, based on the principle of regional autonomy, local governments can exercise powers that are not absolutely the authority of the central government.Therefore, in the future, the regional government authority has a strong legal basis so that the authority regarding corporate social and environmental responsibility is contained in statutory regulations.Keywords: Responsibility, Social, Company, Local Government.